The Mediating Role of Satisfaction between Emotional Values, Social Values, and Behavioral Intentions of Muslim Students - Nurfaizal, Yusmedi; Mustika, Hindah (Ekonomi Syariah IAIN Kudus, 2023)
The study focuses on the behavior of Muslim students’ intentions to revisit halal tourist attractions that have added value. Additionally, it explores the act of revisiting Borobudur Temple as a means of fostering a sense of patriotism and national pride. This study contributes to the existing body of literature on perceived value by investigating the relationship between emotional values, social values, and satisfaction as a mediating factor. The study involves a significant number of participants, including 115 Muslim students living in the Java province. The existing circumstances are transitioning into the new normal, requiring the ongoing implementation of environmental health policies due to the presence of COVID-19. The data analysis utilizing Partial Least Squares (PLS) reveals that emotional and social values have a positive impact on Muslim students’ intention to engage in repetitive behavior. This study also found that there was an indirect influence of the satisfaction variable as a mediation. The primary elements that contribute to enhancing the motives of Muslim students to revisit Borobudur Temple are behavioral intentions and the satisfaction of Muslim visitors. Furthermore, it is essential for stakeholders in tourism-related businesses to enhance awareness and support the development of halal tourism by offering halal tourism services and recognizing its potential as a thriving sector within the tourism industry.